Fellow Eye Deficits in Amblyopia. Issue 3 (3rd July 2019) - Birch, Eileen E.; Kelly, Krista R.; Giaschi, Deborah E.
ABSTRACT: Amblyopia is a neurodevelopmental disorder of the visual system, as a result of discordant visual experience during infancy or early childhood. Because amblyopia is typically defined as monocularly reduced visual acuity accompanied by one or more known amblyogenic factors, it is often assumed that the fellow eye is normal and sufficient for tasks like reading and eye-hand coordination. Recent scientific evidence of ocular motor, visual, and visuomotor deficits that are present with fellow eye monocular viewing and with binocular viewing calls this assumption into question. This clinical update reviews the research that has revealed fellow ocular motor and visual deficits and the effect that these deficits have on an amblyopic child's visuomotor and visuocognitive skills. We need to understand how to prevent and rehabilitate the effects of amblyopia not only on the nonpreferred eye but also on the fellow eye.